Raising awareness and addressing inequities for people with Down syndrome in South Africa - Eimear McGlinchey; Juan Fortea; Bulela Vava; Yvette Andrews; Kirti Ranchod; Atholl Kleinhans (International Journal for Equity in Health)
Abstract Globally, individuals with Down syndrome (DS) face profound inequities in social and health care access. These challenges are further compounded by racial disparities as well as a lack of awareness, research, and support, particularly in the Global South. This commentary discusses the multifaceted challenges and disparities encountered by people with DS in South Africa, highlighting the need for targeted interventions. The paper will summarise the proceedings and outcomes of an imbizo—a strategic gathering of stakeholders in South Africa. This event brought together a diverse group from the DS community, including individuals with DS, their families, healthcare providers, non-profit organizations, and representatives from the Gauteng Department of Health. The discussions at the imbizo were organized into five key thematic areas: Advocacy and Awareness, Inclusion and Engagement, Education, Data and Research, and Networking and Collaboration. Additionally, the paper will underscore the critical need for the establishment of a dedicated DS research network in South Africa. Such a network is envisioned to foster collaboration, facilitate knowledge sharing, and ensure that research initiatives are closely aligned with the needs of the DS community. Overcoming these inequities requires a holistic approach that encompasses policy reforms and the crafting of inclusive services. In its concluding sections, the paper will explore future avenues for creating a sustainable framework aimed at addressing the multifaceted needs of the DS community in South Africa. This initiative represents an effort towards amplifying the well-being, rights, and inclusion of people with DS. Highlighting the necessity of a collaborative and multifaceted approach, this paper proposes a path towards a more inclusive society, advocating for the mitigation of challenges faced by this marginalized community.